The antitumor activity of a doxorubicin loaded, iRGD-modified sterically-stabilized liposome on B16-F10 melanoma cells: in vitro and in vivo evaluation - Yu KF (Dove Medical Press, 2013)
Ke-Fu Yu,1 Wei-Qiang Zhang,1 Li-Min Luo,1 Ping Song,1 Dan Li,1 Ruo Du,1 Wei Ren,1 Dan Huang,1 Wan-Liang Lu,1,2 Xuan Zhang,1 Qiang Zhang1,2 1Department of Pharmaceutics, School of Pharmaceutical Sciences, Peking University, Beijing, People’s Republic of China; 2State Key Laboratory of Natural and Biomimetic Drugs, School of Pharmaceutical Sciences, Peking University, Beijing, People’s Republic of China Abstract: Considering the fact that iRGD (tumor-homing peptide) demonstrates tumor-targeting and tumor-penetrating activity, and that B16-F10 (murine melanoma) cells overexpress both αv integrin receptor and neuropilin-1 (NRP-1), the purpose of this study was to prepare a novel doxorubicin (DOX)-loaded, iRGD-modified, sterically-stabilized liposome (SSL) (iRGD-SSL-DOX) in order to evaluate its antitumor activity on B16-F10 melanoma cells in vitro and in vivo. The iRGD-SSL-DOX was prepared using a thin-film hydration method. The characteristics of iRGD-SSL-DOX were evaluated. The in vitro leakage of DOX from iRGD-SSL-DOX was tested. The in vitro tumor-targeting and tumor-penetrating characteristics of iRGD-modified liposomes on B16-F10 cells were investigated. The in vivo tumor-targeting and tumor-penetrating activities of iRGD-modified liposomes were performed in B16-F10 tumor-bearing nude mice. The antitumor effect of iRGD-SSL-DOX was evaluated in B16-F10 tumor-bearing C57BL/6 mice in vivo. The average particle size of the iRGD-SSL-DOX was found to be 91 nm with a polydispersity index (PDI) of 0.16. The entrapment efficiency of iRGD-SSL-DOX was 98.36%. The leakage of DOX from iRGD-SSL-DOX at the 24-hour time point was only 7.5%. The results obtained from the in vitro flow cytometry and confocal microscopy, as well as in vivo biodistribution and confocal immunofluorescence microscopy experiments, indicate that the tumor-targeting and tumor-penetrating activity of the iRGD-modified SSL was higher than that of unmodified SSL. In vivo antitumor activity results showed that the antitumor effect of iRGD-SSL-DOX against melanoma tumors was higher than that of SSL-DOX in B16-F10 tumor-bearing mice. In conclusion, the iRGD-SSL-DOX is a tumor-targeting and tumor-penetrating peptide modified liposome which has significant antitumor activity against melanoma tumors. Keywords: tumor-targeting and tumor-penetrating, integrin receptor, NRP-1, iRGD, liposome, doxorubicin